Admissible Consensus and Consensualization for Singular Multi-agent Systems - Xi, Jianxiang; Wang, Le; Yang, Xiaogang; Gao, Jiuan; Lu, Ruitao (Engineering Applications of Computational Methods, 2023)
XIX, 272 p. 77 illus., 67 illus. in color.